ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN, SPRINGATE, ZMIJWESKI DAN GROVER PADA PT. INDOFOOD CBP SUKSES MAKMUR TBK PERIODE 2016-2019 - Nurliyana, Nurliyana; Aprialinita, Dhea (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study aims to determine and analyze the level of potential bankruptcy by PT. Indofood CBP Sukses Makmur 2016-2019 period. Bankruptcy of a company can be seen and measured through financial statements, by analyzing financial statements. To research the company, researchers used 4 methods, namely the the method of Altman, Springate, Zmijweski and Grover. This type of research is descriptive quantitative. The source of data used in this study is secondary data. The results of this study indicate that PT. Indofood CBP Sukses Makmur Tbk for the 2016-2019 period has no potential for bankruptcy, because based on the results of the calculation of the four methods, the value exceeds the standard set by the methods.